2020
DOI: 10.1152/ajpendo.00370.2019
|View full text |Cite
|
Sign up to set email alerts
|

Combined overexpression of SIRT1 and knockout of GCN5 in adult skeletal muscle does not affect glucose homeostasis or exercise performance in mice

Abstract: Sirtuin 1 (SIRT1) and general control of amino acid synthesis 5 (GCN5) regulate mitochondrial biogenesis via opposing modulation of peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) acetylation status and activity. However, the combined contribution of SIRT1 and GCN5 to skeletal muscle metabolism and endurance performance in vivo is unknown. In this study, we investigated the impact of combined skeletal muscle-specific overexpression of SIRT1 and deletion of GCN5 on glucose homeostasis, skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…Researchers further generated skeletal muscle-specific SIRT1-mKO mice and found that mKO mice lost the effect of CR-induced increasing insulin sensitivity and were unable to deacetylate and inactivate STAT3, resulting in upregulating the phosphatidylinositol-3-kinase (PI3K) inhibitory regulator p55α/p50α expression (Schenk et al, 2011). Although knockout or overexpression of SIRT1 in skeletal muscles has no effect on endurance capacity or glucose homeostasis in mice (Gurd et al, 2009;Philp et al, 2011;White et al, 2013;Svensson et al, 2020), some studies have shown that AMPK regulates energy metabolism of skeletal muscles partially mediated by SIRT1, and SIRT1 is significantly increased after endurance exercise (Suwa et al, 2008;Canto et al, 2009). Overexpression of Sirt1 in skeletal muscles by adeno-associated virus 1 (AAV1) promotes the expression of oxidation-related genes including Ppargc1a, Tfam, Cpt1b, and Pdk4, while it has no effect on insulin sensitivity of body (Vila et al, 2016).…”
Section: Class III Hdacs/sir2-homolog: Sirt1/6/3/4 Nuclear-located Simentioning
confidence: 99%
“…Researchers further generated skeletal muscle-specific SIRT1-mKO mice and found that mKO mice lost the effect of CR-induced increasing insulin sensitivity and were unable to deacetylate and inactivate STAT3, resulting in upregulating the phosphatidylinositol-3-kinase (PI3K) inhibitory regulator p55α/p50α expression (Schenk et al, 2011). Although knockout or overexpression of SIRT1 in skeletal muscles has no effect on endurance capacity or glucose homeostasis in mice (Gurd et al, 2009;Philp et al, 2011;White et al, 2013;Svensson et al, 2020), some studies have shown that AMPK regulates energy metabolism of skeletal muscles partially mediated by SIRT1, and SIRT1 is significantly increased after endurance exercise (Suwa et al, 2008;Canto et al, 2009). Overexpression of Sirt1 in skeletal muscles by adeno-associated virus 1 (AAV1) promotes the expression of oxidation-related genes including Ppargc1a, Tfam, Cpt1b, and Pdk4, while it has no effect on insulin sensitivity of body (Vila et al, 2016).…”
Section: Class III Hdacs/sir2-homolog: Sirt1/6/3/4 Nuclear-located Simentioning
confidence: 99%
“…Exercise as well as diets can activate the AMPK/SIRT1/PGC1α axis [ 583 , 584 , 585 , 592 , 597 , 598 , 599 ]. Resveratrol and telmisartan activate the SIRT1/PGC1α and AMPK/SIRT1 pathways, to increase mitochondrial activity and aerobic capacity in muscle cells, respectively [ 589 , 590 ]. In addition, hyperinsulinemia increases SIRT1 expression in muscle tissue [ 610 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in mice, upregulation of SIRT1 alone is not correlated to an enhanced glucose homeostasis or to mitochondrial biogenesis as compared to wild type during exercise training [ 590 ]. This observation indicates that, even though SIRT1 is upregulated during exercise in skeletal muscle, increased levels do not mediate an enhanced response.…”
Section: The Role Of Sirtuins In Metabolic Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…From these findings arose the hypothesis that GCN5 deletion could drive PGC-1αdirected mitochondrial biogenesis in muscle. However, recent work could not identify a metabolic role for GCN5 in skeletal muscle (Dent et al, 2017;Svensson et al, 2020).…”
Section: Introductionmentioning
confidence: 96%